Vitamin D deficiency is associated with poor breast cancer prognostic features in postmenopausal women - de Sousa Almeida-Filho, Benedito [UNESP] (2017)
This study aimed to evaluate the association between pretreatment vitamin D (VD) deficiency with breast cancer prognostic features in Brazilian postmenopausal women. An analytical cross sectional study was conducted with 192 women, aged 45–75 years, attended at University Hospital. Women with recent diagnosis of breast cancer, in amenorrhea >12 months and age ≥45 years, without medication use or clinical conditions that interfere with VD values were included. Clinical and anthropometric data were collected. Serum level of 25 hydroxyvitamin D [25(OH)D] was measured in all patients until 20 days after breast cancer diagnosis, and was classified as normal (≥30 ng/mL), insufficiency (20–29 ng/mL) and deficiency (<20 ng/mL). Data on breast cancer (histopathological type, grade, tumor stage, lymph node status), hormone status (estrogen receptor, ER, progesterone receptor, PR), human epidermal growth factor receptor type 2 (HER2) and epithelial proliferative activity (Ki-67) were collected. For statistical analysis, the t-student test, the Gamma Distribution (asymmetric variables), the chi-square test and the logistic regression (OR-odds ratio) were used. The median 25(OH)D level was 25.8 ng/mL (range 12.0–59.2 ng/mL). Sufficient vitamin D levels were detected in 65 patients (33.9%), whereas insufficient levels in 92 patients (47.9%), and deficient levels in 35 patients (18.2%). Participants with insufficient and deficient 25(OH)D levels had a higher proportion of tumors with a high grade and locally advanced and metastatic disease, more positive lymph node, a lower proportion of ER, PR positives tumors and higher Ki-67(p < 0.05). Patients with normal vitamin D had a higher frequency of luminal A (47.7%) and luminal B (32.2%) tumors when compared to patients with vitamin D insufficiency or deficiency. Furthermore, all cases of triple negative were detected in women with low VD levels. Multivariate analysis, after adjusting for age, time since menopause and BMI, showed that insufficient and deficient level of vitamin D were significantly associated with negative estrogen receptor (OR 3.77 CI 95% 1.76–8.09 and OR 3.99 CI 95% 1.83–8.68), high Ki-67 (OR 2.50, CI 95% 1.35–4.63, and OR 2.62, CI 95% 1.40–4.98), and positive axillary lymph node status (OR 1.59, CI 95% 1.03–2.33, and OR 1.58, CI 95% 1.02–2.92) respectively. In Brazilian postmenopausal women with breast cancer, there was an association between vitamin D insufficiency or deficiency and tumors with worse prognostic features. Low vitamin D levels were shown to be a risk factor for ER negative tumors, with positive axilla and a higher rate of cell proliferation.